2009
DOI: 10.1246/cl.2009.914
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ArSE Aroylation of Naphthalene Derivatives

Abstract: Reversible ArSE aroylation has been observed in the reaction of 2,7-dimethoxynaphthalene (1) with 4-chlorobenzoic acid/acid chloride 2 with the aid of discrete acidic mediators. The reaction readily gives 1-aroylated-, 3-aroylated-, and 1,8-diaroylated products. The product distribution clearly shows dependence on the kind and strength of the acidic mediators and the time-course of the distribution manifests dearoylation of the productive aroylnaphthalenes. These reaction behaviors including acid-strength-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 15 publications
0
85
0
Order By: Relevance
“…22 Synthetic methods and spectral data for the precursor, 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene, have been reported in literature. 11,12,20 Measurements 1 H NMR spectra were recorded on a JEOL JNM-AL300 spectrometer (300 MHz). Chemical shifts are expressed in ppm relative to internal standard of Me4Si (δ 0.00).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Synthetic methods and spectral data for the precursor, 1,8-bis(4-chlorobenzoyl)-2,7-dimethoxynaphthalene, have been reported in literature. 11,12,20 Measurements 1 H NMR spectra were recorded on a JEOL JNM-AL300 spectrometer (300 MHz). Chemical shifts are expressed in ppm relative to internal standard of Me4Si (δ 0.00).…”
Section: Methodsmentioning
confidence: 99%
“…The authors' recent work has focused on peri-aroylnaphthalene compounds and the homologous/analogous substances. [11][12][13][14][15][16][17][18][19][20] According to the X-ray crystal structural analyses of ninety peri-aroylnaphthalene compounds, the two aroyl groups are non-coplanarly situated to the naphthalene ring and ordinary oriented in an opposite direction (anti-orientation). The molecular packing of peri-aroylnaphthalene compounds are mainly stabilized by cooperation of several kinds of weak non-covalent-bonding interactions, i.e., four kinds of nonclassical hydrogen bonds, (sp 2 )C-H···O=C hydrogen bond, (sp 3 )C-H···O=C hydrogen bond, (sp 3 )C-H···OR hydrogen bond, and C-H···π hydrogen-bonding interaction, and π···π stacking interaction are observed in decreasing order of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…For the formation reaction of aroylated naphthalene compounds via electrophilic aromatic aroylation of 2,7-dimethoxynaphthalene, see: Okamoto & Yonezawa (2009). For related structures, see: Muto et al (2010); Nakaema et al (2007Nakaema et al ( , 2008; Watanabe et al (2010a,b).…”
Section: Related Literaturementioning
confidence: 99%
“…From this point of view, the naphthalene derivatives having aroyl groups at peri-positions, i.e., 1-aroyland 1,8-diaroylnaphthalene derivatives, are one of the good models for analysing non-covalent bonding interactions in crystal. Recently, the authors have found highly effective diaroylation at peri (1,8)-positions of 2,7-dialkoxynaphthalene [10,11]. Furthermore, functional group interconversion of 2-and/or 7-alkoxy group to hydroxyl group is also achievable [12].…”
Section: Introductionmentioning
confidence: 99%